Literature Study on Microorganism-Based Biosensor Applications for Real-Time Water Quality Monitoring - Ananta, Yorasakhi; Fitri , Salsabila Dwi (Dinasti Information and Technology, 2025)
The effect of microbial biosensors and real-time systems on water quality monitoring is a scientific article in the study of literature within the scope of environmental biotechnology. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects were sourced from online libraries, Google Scholar, Mendeley, and other academic online media. The research method is a research library sourced from e-books and open-access e-journals. The results of this article are microbial biosensors have an effect on water quality monitoring, and then real-time systems have an effect on water quality monitoring.